Faktor mempengaruhi Nilai Perusahaan pada Sub Sektor Makanan dan Minuman di BEI - Anggi Dwi Pratiwi; Beny Beny (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to test and analyze the effect of investment decisions, funding decisions, dividend policy, firm size, profitability, and liquidity on company’s value. The research sample used was companies listed in the food and beverages subsector in Indonesia Stock Exchange for the period 2010-2020. The sampling method in this purpose used purposive sampling. With this sampling method used purposive sampling, there were 7 companies that meet the sampling criteria and 77 data were obtained to be used as samples. The research method used in this study was descriptive statistics, and panel data regression, with the chose model the fixed effect model. The result of this study indicate that investment decisions and firm size have a positive effect on company’s value. While funding decisions, dividend policy, profitability, and liquidity do not affect compan’s value.